Foundational Data Science Training for Health Equity Researchers at Minority Serving Institutions: A SoRDS Event - Quick, Robert; Córdoba, Marcela Alfaro; Diggs, Stephen; Cobe, Raphael [UNESP]; Bezuidenhout, Louise; Shannahan, Hugh; Peterson, Bianca (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Contemporary research, particularly when addressing the most significant transdisciplinary research challenges, cannot effectively be done without a range of skills relating to data management, data analysis, and cyberinfrastructure (CI). These data and CI skills are common to all disciplines that conduct data-centric research. Research Data Science acts as a vital component of the scientific process. In a grassroots attempt to address this gap, the CODATA-RDA Schools of Research Data Science (SoRDS) was founded in 2016 to provide instruction on foundational data science and open research concepts to early career researchers in low and middle-income countries. This partnership between international collaborators has since 2016 provided this training to over 1000 early career researchers in 24 events in 10 countries worldwide. The most recent event was held at Georgia Institute of Technology and focused on health equity and included researchers from minority-serving institutions in the southeast United States. This paper covers the background of the SoRDS project along with organization and curriculum details. It also covers the transition of the events from a non-domain-centric curriculum to spotlighting biological and social health equity data and what we learned to make future health-related events more engaging and valuable to the attendees. It also looks toward future events that will serve international students studying health informatics and other data-centric disciplines.
Keywords: curriculum development; data-centric research; ethical data use; health equity; minority serving institutions; minority-led research; open data; training